STAN PASAR SEBAGAI JAMINAN BERDASARKAN PERJANJIAN TENTANG PEMBERIAN HAK MEMAKAI RUANG (STAN) DI BANK CENTRAL ASIA - Rianti, Novia (Legality : Jurnal Ilmiah Hukum, 2018)
Space rights agreement is a part of lease agreement. Leasing is an agreement that gives a right called individual rights. It is because the right to lease arises from an agreement between one legal subject to another. Thus, this right can only be accountable to the opponent of the contract in accordance with the principle of privity of contrac. A lease agreement aims at providing the right only to use the property, and not to own it. Therefore, lease agreement only gives individual rights, not property rights. On the other hand, as we know, fiduciary provides object guarantees, which is included in constitutum possessorium (the object transferred remains within the control of the fiduciary giver). The air rights, the market stall, from the agreements of rights granting, are clearly included in individual rights, rather than property, which should not be imposed on fiduciary guarantees. This research is conducted by applying doctrinal research. It adapts statute approach, conceptual approach, and case study for its methodological problem approach. This study analyzes the market stall usage rights as an object from the perspective of security laws and Fiduciary on the usage rights upon a market stall by banks. The results of the research showed that by reviewing it further using air rights perspective, the air rights upon a market stall were included in lease rights. The right to use the stall is not property rights, but is an individual right. It is based on the law of lease rights. In addition, the debtor, as the tenant, only controls the leased objects to make use of it, not for the purpose of owning it. In that way, the lease itself does not result in property rights. However, if it is reviewed further based on the air rights, this can be categorized as an object with security laws, because the air rights fulfill the requirements as an object that can be guaranteed. It is because it has economic value and can be transferred, even though it is approved by another party. Since the air rights are individual right, it cannot be used as a guarantee for pawn, mortgage, and Fiduciary.